HUBUNGAN PEMBERIAN EDUKASI SWAMEDIKASI OBAT ANTINYERI DENGAN KEPUASAN PASIEN DI APOTEK BLUNYAH FARMA - Vita Angraini; Ria Etikasari; Muhammad Khudzaifi (Nusantara Hasana Journal, 2025)
Self-medication, particularly for pain, is becoming increasingly common. However, most patients still lack adequate understanding of the types of medications, dosages, and potential risks. Therefore, education provided by pharmacists plays a crucial role in improving patient understanding and satisfaction with the rational use of painkillers. This study aimed to determine the relationship between self-medication education on painkillers and patient satisfaction at Blunyah Farma Pharmacy, Sleman Regency, Yogyakarta. The study used a quantitative observational method with a cross-sectional design. The independent variable was self-medication education on painkillers, while the dependent variable was patient satisfaction. Data were collected through questionnaires completed directly by patients purchasing painkillers. The study sample consisted of 300 respondents from a total population of 1,200, with a margin of error of 5%. The results showed that the majority of respondents received high levels of education (57.7%) and expressed very high levels of satisfaction with the services they received (40.3%). A Spearman Rank correlation test using SPSS version 22 showed a very strong and significant relationship between the two variables, with a correlation coefficient of 0.941 and a significance level of 0.000 (<0.05). Therefore, the better the quality of education provided, the higher the patient satisfaction level.